Hip strength assessment using handheld dynamometry is subject to intertester bias when testers are of different sex and strength. Issue 4 (28th October 2011) - Thorborg, K.; Bandholm, T.; Schick, M.; Jensen, J.; Hölmich, P.
Abstract : Handheld dynamometry (HHD) is a promising tool for obtaining reliable hip strength measurements in the clinical setting, but intertester reliability has been questioned, especially in situations where testers exhibit differences in upper‐extremity muscle strength (male vs female). The purpose of this study was to examine the intertester reliability concerning strength assessments of hip abduction, adduction, external and internal rotation, flexion and extension using HHD, and to test whether systematic differences in test values exist between testers of different upper‐extremity strength. Fifty healthy individuals (29 women), aged 25 ± 5 years were included. Two physiotherapist students (one female, one male) of different upper‐extremity strength performed the measurements. The tester order and strength test order were randomized. Intraclass correlation coefficients were used to quantify reliability, and ranged from 0.82 to 0.91 for the six strength test. The female tester systematically measured lower strength values for all isometric strength tests ( P  < 0.05). In hip strength assessments using HHD, systematic bias exists between testers of different sex, which is likely explained by differences in upper‐extremity strength. Hence, to improve intertester reliability, the dynamometer likely needs external fixation, as this will eliminate the influence of differences in upper‐extremity strength between testers.